2020
DOI: 10.11648/j.jfns.20200804.17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Beetroot Bulbs (Beta <i>vulgaris</i>) from Selected Geographical Regions in Kenya: Essential Nutritional Elements Contents

Abstract: In Kenya, beetroot bulbs are occasionally used as a blend in fruit juices and salads, as a livestock feed and for treatment of diseases. Analysis of essential elements in beetroot bulbs was performed using Energy Dispersive X-ray fluorescence (EDXRF) in order to determine the nutritional content of the bulbs. The beetroot bulbs were sampled from five different geographical regions in Kenya; Karatina, Gilgil, Naivasha, Joska and Kisumu. The results of the concentrations of the essential elements had a range of:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The concentration of Ag, Co, Cr, Li, Mo, Ni, Pb in conventional and organic beetroots samples were determined under the LOQ ( Table 4 ). The observed variability in the analysed mineral concentration might be a result of the differences in plants’ geographical origin [ 34 ], fertilization [ 35 , 36 ], as well as varietal differences [ 37 ]. In the case of dietary supplements, Se, Cu, Ag, Co, Cr, Ba, Li, Mo, Ni, Pb concentrations were under the LOQ ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Ag, Co, Cr, Li, Mo, Ni, Pb in conventional and organic beetroots samples were determined under the LOQ ( Table 4 ). The observed variability in the analysed mineral concentration might be a result of the differences in plants’ geographical origin [ 34 ], fertilization [ 35 , 36 ], as well as varietal differences [ 37 ]. In the case of dietary supplements, Se, Cu, Ag, Co, Cr, Ba, Li, Mo, Ni, Pb concentrations were under the LOQ ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…16 EDXRF [16] Ocimum gratissimum 2100 to 3700 77 to 190 12 to 16 127 to 130 AAS [31] Kale 211.54 ± 94.06 211.54 ± 94.06 5.24 ± 2.49 40 ± 18.67 AAS [32] Cabbage 87.41 ± 38. 25 15.61± 6.71 4.73 ± 2.97 30.65 ± 13.89 AAS [32] Spinach 301.30 ± 43.07 142.18 ± 70.22 4.89 ± 1.98 61.42 ± 25.39 AAS [32] Beetroot bulbs 53 to 420 24 to 770 -16 to 680 EDXRF [33] Finger millet 127 to 259 95 to 290 <7.47 to 16 13 to 52 EDXRF [34] Medicinal plants 17.35 to 78.65 18. 20 to 33.56 0.51 to 1.98 5.65 to 7.31 EDXRF [35] African indigenous leafy vegetables 130 to 1010 --30 to 100 EDXRF [14] Note: AAS, atomic absorption spectrometry; EDXRF, energy dispersive X-ray fluorescence, TXRF, total reflection X-ray fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies of urban and peri-urban farming worldwide have demonstrated that it effectively improves household food security (Michailidis, D.L. and D. Lazaridou, 2020, Moorthy, D., et al, 2020, Ndunge, G., et al, 2020. Peri-urban farming is also practical as an income-generating activity (Ndunge, G., et al, 2018).…”
Section: Alternative Farming For Food Security In Urban Areasmentioning
confidence: 99%
“…According to a study conducted by Ndunge, G., et al, (2020), nearly 73,000 children in Kenya were severely malnourished and at risk of dying from drought-related hunger. The survey also revealed that almost 40,000 pregnant and nursing women across Kenya were malnourished, a 20% increase from 2016, leaving them and their children's health in a precarious position, says.…”
Section: Formation and Objective Of "Tule Vyema" Community-based Orga...mentioning
confidence: 99%